<>. - Jun, Li (China Intercontinental Press, 2015)
While it is impossible for the mankind to eliminate disasters and sufferings, the humanitarian relief operations manifest the brilliance of humanity and the power of nations. China's Humanitarian Relief Operations tells about six of the major relief operations that have happened in and outside China: the anti-SARS operations, the fight against the snow disaster, the Wenchuan earthquake relief operations, the Yushu earthquake relief operations, the Indian Ocean Tsunami relief operations, and the evacuation of Chinese citizens from Libya. The lively scenes, the heroic figures and events of human.